2022
DOI: 10.1001/jamanetworkopen.2022.27348
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Clinical and Virological Characteristics of SARS-CoV-2 Infection Among Children Aged 0 to 4 Years and Their Household Members

Abstract: IMPORTANCEFew studies have prospectively assessed SARS-CoV-2 community infection in children aged 0 to 4 years. Information about SARS-CoV-2 incidence and clinical and virological features in young children could help guide prevention and mitigation strategies. OBJECTIVE To assess SARS-CoV-2 incidence, clinical and virological features, and symptoms in a prospective household cohort and to compare viral load by age group, symptoms, and SARS-CoV-2 lineage in young children, older children, and adults. DESIGN, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…9 In addition, vaccination against SARS-CoV-2 has been reported to prevent progression to multisystem inflammatory syndrome in children among adolescent patients during the period when Delta and Omicron variants were circulating. 10 The prospective household cohort study by Karron et al 4 found that young children are important reservoirs of SARS-CoV-2 infection and that relying on symptom-based testing may not be enough to mitigate the transmission of SARS-CoV-2 among children aged 0 to 4 years, an age group that now has safe and beneficial vaccines available for use. Vaccination against SARS-CoV-2 will likely be the best strategy to diminish the spread of virus and prevent severe disease in children.…”
Section: + Related Articlementioning
confidence: 99%
See 2 more Smart Citations
“…9 In addition, vaccination against SARS-CoV-2 has been reported to prevent progression to multisystem inflammatory syndrome in children among adolescent patients during the period when Delta and Omicron variants were circulating. 10 The prospective household cohort study by Karron et al 4 found that young children are important reservoirs of SARS-CoV-2 infection and that relying on symptom-based testing may not be enough to mitigate the transmission of SARS-CoV-2 among children aged 0 to 4 years, an age group that now has safe and beneficial vaccines available for use. Vaccination against SARS-CoV-2 will likely be the best strategy to diminish the spread of virus and prevent severe disease in children.…”
Section: + Related Articlementioning
confidence: 99%
“…The study by Karron et al 4 revealed the importance of SARS-CoV-2 infection in children, although several limitations of the study were noted by the authors. The first was that the study does not necessarily represent the general population; for example, 87.4% of the study population selfreported their race as White, and household members required online access to enter study data.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…However, the clinical significance in children and adolescents has remained stably low compared to that in adults and elderlies [ 4 ]. In addition, asymptomatic infection is common in children [ 5 ]. The reason for this is still not clearly explained, but recent exposure to other viruses and routine vaccines—including but not limited to Bacillus Calmette–Guérin (BCG), measles-mumps-rubella (MMR), and tetanus-diphtheria-pertussis (Tdap) in children—are presumed to be associated with protective cross-reactive antibodies and T cells against SARS-CoV-2, based on a recent study [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although children are susceptible to SARS-CoV-2 infection and can transmit the virus to others [ 2 ], relatively few studies have focused on disease characteristics and patterns of transmission among children aged 0–4 years. Children are more frequently asymptomatic or mildly symptomatic compared with adults [ 3 ], and some household studies have found asymptomatic transmission to be significantly lower than symptomatic transmission [ 4 , 5 ]. Because children are more likely to be asymptomatic when infected with SARS-CoV-2, they are also less likely to be tested, and their infections are less likely to be detected.…”
mentioning
confidence: 99%